Exploring the Implementation of Ethical and Spiritual Values in High School Education: A Case Study in Makassar, Indonesia - Mulang, Hastuti; Putra, Aditya Halim Perdana Kusuma (Golden Ratio of Social Science and Education, 2023)
This research explores the implementation of Islamic ethical and spiritual values in high school students using a case study design and qualitative research approach. Data was collected through observation, interviews, and documentation from 19 informants, including school officials, students, and parents. The research findings indicate that educators instill ethical and spiritual values in students as part of the process of character development, which starts from planning, execution, and evaluation phases outlined in the Lesson Preparation Plan (RPP) to produce students with high morals, faith, and piety. The study highlights the importance of instilling ethical and spiritual values in high school students to develop their character and help them become more morally upright, faithful, and pious individuals. The cultivation of ethical and spiritual values cannot be separated from supportive and inhibiting factors. The commitment of the school principal and the provision of facilities and infrastructure are supportive factors, while modern technological developments, poor social environment, and lack of attention from parents are inhibiting factors. The findings underscore the need for schools to provide the necessary support and infrastructure to ensure the successful implementation of such values. This study provides valuable insights into the factors that support or hinder the process of instilling ethical and spiritual values in high school students.